PELATIHANKERAJINANTANGANDARIKAINFLANELSEBAGAIPEMBERDAYAAN - Mahrus Ali (UII, 2013)
Honing creativity is necessary because of the importance to our success.Creativity is not just belong to the artist, but all aspects of life will require creative abilityto solve problems and get ideas that improve your career, business and life. Creativitykeep the passion and creativity makes life kept going. As has been discovered that theaverage working mothers in addition to taking care of the home and children is alsoworking to help her husband make sugar or grazing. Activities that take place every dayto make mothers less developed ability creativity. This training aims to develop thecreative abilities of households mothers so that later can increase family income.Conducting training programs crafts of flannel as empowerment through the followingsteps; identification of the subject to do counseling, counseling and fabrics as well aspattern recognition, pattern making and sewing, start stringing forms, evaluation. Giventhese activities can make mothers creativity with flannel and add to their daily activities.